Innovative technologies and learning : Second International Conference, ICITL 2019, Tromsø, Norway, December 2-5, 2019, proceedings /: Second International Conference, ICITL 2019, Tromsø, Norway, December 2-5, 2019, proceedings. ([2019]) - Unknown
No abstract available